Cu(II) ions removal from wastewater using starch nanoparticles (SNPs): An eco‐sustainable approach. (14th September 2022) - Hakke, Vikas S.; Landge, Vividha K.; Sonawane, Shirish H.; Babu, G. Uday Bhaskar; Manickam, Sivakumar; Boczkaj, Grzegorz
Abstract: The complex structured starch particles were reduced to the nanoscale size range through hydrolysis utilizing low concentration acid assisted by ultrasound irradiation. The synthesized starch nanoparticles (SNPs) were characterized by transmission electron microscopy (TEM), Fourier‐transform infrared (FTIR), and X‐ray diffraction (XRD) techniques. The synthesized SNPs possessed surface activated entities, as many cationic functional groups were confirmed through the FTIR spectrum. Also, these SNPs were effectively utilized to separate heavy Cu metal ions from the synthetic ion solution. The SNPs were characterized using field emission scanning electron microscope (FESEM), X‐ray photoelectron spectroscopy (XPS), and Brunauer–Emmett–Teller (BET) analysis for the surface modification after the adsorption process. The weak electrostatic interaction between the SNP surface and Cu ion was confirmed by the XPS spectrum and energy‐dispersive X‐ray spectroscopy. The maximum efficiency of Cu ions removal was about 93% at an optimal pH 5 and 25 mg/ml dosage. The adsorption equilibrium was obtained in 60 min. The nitrogen isotherm BET analysis of SNPs after adsorption shows a higher specific surface area of 18.552 m 2 /g, attributed to the interaction and presence of Cu ions on the SNP surface. The process feasibility was validated by the Langmuir isotherm model. The process exhibits pseudo‐second‐order adsorption kinetics and follows the Langmuir isotherm. The R L predicted by the Langmuir isotherm mechanism is 0.017, implying favourable adsorption. The process is reproducible and allows for the separation of heavy metal ions from the wastewater through biosorption effectively. Abstract :